Migrant Labour Mobility And The Right To Portable Social Security In Asean Countries: A Legal Perspective - Rahim, Rohani Abdul; Hassan, Kamal Halili; Basir, Salawati Mat; Tajuddin, Muhammad Afiq Ahmad; Bakar, Kamaruddin Abu (Universiti Sains Malaysia, 2016)

(untitled)
Each year estimated six million currently residing in other ASEAN member states. The majority of migrants are low-skilled, and many are irregular. Cambodia, Lao Democratic People’s Republic,Myanmar, Indonesia, Viet Nam and the Philippines are identified as the sending countries while Singapore, Thailand, Malaysia and Brunei Darussalam are the receiving countries. As mentioned by the ILO (International Labor Organization), migration should be a choice rather than a necessity. While migration may provide a route out of poverty, it is important to balance the promotion of migration with appropriate protection measures. The 2007 Declaration on the rights of migrant workers acknowledges the obligation for receiving states to “facilitate access to justice and social welfare states as appropriate and in accordance with the national legislation of the receiving state” and to “promote fair and appropriate employment protection, payment of wages, and adequate access to decent working and living conditions” (ASEAN, 2007: §7 & §8). However, the concern is that the Declaration contains no explicit actions towards the establishment of portability schemes for social security benefits. This paper will explore on the reasons why portable social security would be the means to enable the free –flow of goods, services, investment, labors (skilled and low-wages) and capital in this region as envisage in the ASEAN Blueprint planning. Social security being a form of social protection is upheld as a migrant labor right by the International Labor Organization, and its establishment is a necessity and await by all migrant labors. The paper will also determine the possible ways how the portable schemes can be accomplished and taking into account the state members’ sovereignty and delimitation concurrently. Migration management strengthening and protecting the rights of migrants may become the decisive approach in understanding the need for a portable social security which corresponds to the ASEAN Economic enhancement goals.